2019
DOI: 10.1097/jcn.0000000000000531
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Types of Social Support, Coping Strategies, and Psychological Distress in Individuals Living With Congenital Heart Disease

Abstract: Thank you for taking my side even when I was at fault….

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 179 publications
(268 reference statements)
2
10
0
Order By: Relevance
“…As we expected, COVID-19-specific wishful thinking, a negative EFC strategy, plays a mediating role in the relationship between perceived threat avoidability and psychic anxiety. Consistent with prior findings, we confirm that when individuals perceive a high level of threat avoidability, they will reduce wishful thinking ( 36 ) and experience a low level of anxiety symptoms ( 43 , 64 ). Furthermore, our results support the mediating effect of COVID-19-specific protective behaviors, a positive PFC strategy, in the relationship between perceived threat avoidability and psychic anxiety.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As we expected, COVID-19-specific wishful thinking, a negative EFC strategy, plays a mediating role in the relationship between perceived threat avoidability and psychic anxiety. Consistent with prior findings, we confirm that when individuals perceive a high level of threat avoidability, they will reduce wishful thinking ( 36 ) and experience a low level of anxiety symptoms ( 43 , 64 ). Furthermore, our results support the mediating effect of COVID-19-specific protective behaviors, a positive PFC strategy, in the relationship between perceived threat avoidability and psychic anxiety.…”
Section: Discussionsupporting
confidence: 90%
“…In the context of the COVID-19 pandemic, when people perceive that the threat is avoidable and the harm can be avoided through some measures, they will reduce the use of EFC such as wishful thinking ( 36 ). At the same time, previous studies have shown that wishful thinking negatively affects individuals’ mental health ( 41 ), is predictive of negative emotions ( 34 ), and increases the levels of anxiety ( 42 , 43 ). Based on this, we propose the following hypothesis:…”
Section: Hypotheses Developmentmentioning
confidence: 94%
“…65 Studies from North America, Germany, and France that incorporated structured clinical interviews observed current 3 or lifetime 2,66 prevalence rates of mood or anxiety disorders of ≈50%. Known risk factors for depression and anxiety among adults with congenital heart disease include poorer neurocognitive functioning (eg, executive function), 29 loneliness, 2 limited social support, 67 poorer perceived health status, 2 and sedentary behavior. 68…”
Section: Psychological Outcomes Across the Life Spanmentioning
confidence: 99%
“…Furthermore, coping style, such as seeking advice from others, is positively associated with subjective and utilization of support. The buffering effects of social support on emotional distress are often mediated by the coping behaviors ( 41 ). For instance, research on pregnant women demonstrated that positive coping and subjective and utilization of support acted as chain mediators on the link of neuroticism and depressive symptoms after earthquake ( 42 ) as well as on the link of childhood abuse and emotional distress among them ( 43 ).…”
Section: Introductionmentioning
confidence: 99%